Opening the black box of diagnosis-related groups (DRGs): unpacking the technical remuneration structure of the Dutch DRG system. Issue 2 (27th April 2020) - van Herwaarden, Sam; Wallenburg, Iris; Messelink, Joris; Bal, Roland
Abstract: While we know that upcoding of diagnosis-related groups (DRGs) regularly occurs, we have little knowledge of the role of the technical features of coding systems in inducing coding behaviour. This paper presents methods for investigating the financial structure of the Dutch DRG system, and more in particular the grouper software, to gain such insight. The paper describes a system for investigating the robustness of the reward structure, by simulating the response of the DRG system to small changes in individual coding. The results from these analyses are used to visualise some data on coding behaviour, and to investigate how this behaviour is affected by incentives in the technical features of the DRG system. A number of technical weaknesses in the system are also identified.